LncRNA MALAT1 induces colon cancer development by regulating miR‐129‐5p/HMGB1 axis - Wu, Qiong; Meng, Wen‐Ying; Jie, Ying; Zhao, Haijian (Journal of cellular physiology, 2018)
Recent studies have exhibited significant roles of lncRNAs in various tumors' development, including colon cancer. Our study focused on the biological roles of lncRNA MALAT1 in colon cancer. In our study, it was demonstrated that MALAT1 was upregulated in human colon cancer cell lines including Lovo, HCT116, SW480, and HT29 cells compared to the normal human intestinal epithelial HIEC cells. Moreover, we observed that miR‐129‐5p was downregulated in colon cancer cells with a significant increase of HMGB1 expression. Inhibition of MALAT1 can inhibit the proliferation of colon cancer SW480 and HCT116 cells and next, bioinformatics analysis was used to predict the target microRNA of MALAT1. miR‐129‐5p was identified and confirmed as a direct regulator of MALAT1 and it was shown that miR‐129‐5p mimics were able to restrain the progression of colon cancer cells. In addition, high motility group box protein 1 (HMGB1), was predicted as a mRNA target of miR‐129‐5p. Furthermore, we found that MALAT1 exerted its biological functions through regulating HMGB1 by sponging miR‐129‐5p in vitro. Silencing MALAT1 greatly inhibited HMGB1 expression which can be reversed by miR‐129‐5p inhibitors. It was indicated in our investigation that MALAT1 may serve as a competing endogenous lncRNA (ceRNA) to mediate HMGB1 by sponging miR‐129‐5p in colon cancer. Taken together, our results indicated that MALAT1/miR‐129‐5p/HMGB1 axis could be provided as an important prognostic biomarker in colon cancer development. We found that MALAT1 can be identified as an oncogene in colon cancer development, and for the first time, we reported a novel mechanism for MALAT1 in colon cancer. Our results revealed that MALAT1/miR‐129‐5p/HMGB1 axis was involved in colon cancer and can act as a therapeutic indicator.